Vocal Parameters of Speech and Singing Covary and Are Related to Vocal Attractiveness, Body Measures, and Sociosexuality: A Cross-Cultural Study - Valentova, Jaroslava Varella; Tureček, Petr; Varella, Marco Antonio Corrêa; Šebesta, Pavel; Mendes, Francisco Dyonisio C.; Pereira, Kamila Janaina; Kubicová, Lydie; Stolařová, Petra; Havlíček, Jan (Frontiers in Psychology, 2019)
Perceived vocal attractiveness and measured sex-dimorphic vocal parameters are both associated with underlying individual qualities. Research tends to focus on speech but singing is another highly evolved communication system that has distinct and universal features with analogues in other species, and it is relevant in mating. Both speaking and singing voice provides relevant information about its producer. We tested whether speech and singing function as ‘backup signals’ that indicate similar underlying qualities. Using a sample of 81 men and 86 women from Brazil and the Czech Republic, we investigated vocal attractiveness rated from speech and singing and its association with fundamental frequency (F0), formant frequencies (VTL), body characteristics, and sociosexuality. F0, VTL, and rated attractiveness of singing and speaking voice strongly correlated within the same individual. Lower-pitched speech in men, higher-pitched speech and singing in women, individuals who like to sing more, and both male and female signing voices with a higher pitch modulation were more attractive. In men, physical size positively predicted speech and singing attractiveness. Male speech but not singing attractiveness was associated with higher sociosexuality. Lower-pitched male speech was related to higher sociosexuality, while lower-pitched male singing was linked to lower sociosexuality. Similarly, shorter speech VTL and longer singing VTL predicted higher sociosexuality in women. Different vocal displays function as ‘backup signals’ cueing to attractiveness and body size, but their relation to sexual strategies in men and women differs. Both singing and speech may indicate evolutionarily relevant individual qualities shaped by sexual selection.